Days of heaven - Morricone, Ennio 1928-2020 (The Criterion Collection, 2007)
In 1910, Bill, a Chicago steel worker accidentally kills his supervisor. He flees to the Texas panhandle with his lover Abby and little sister Linda, where they work harvesting wheat in the fields of a stoic farmer. When Bill learns that the Farmer is ill and has less than a year to live, he encourages Abby to accept the man's attentions. The Farmer and Abby marry, and she and her "siblings" live in the big house, waiting for the Farmer to die, so Abby can inherit, and the three of them live happily ever after. But love seems to be a cure-all: the Farmer seems to be improving--and Abby is no longer seeing this as a marriage of convenience. From a landscape of panoramic vistas, vivid colors, and rich textures comes a timeless American idyll and a gritty evocation of turn-of-the-century labor.
Aspect ratio 1.78:1, 16:9 widescreen. - New, restored high-definition digital transfer, supervised and approved by director Terrence Malick, editor Billy Weber, and camera operator John Bailey
Orig.: USA 1978
Enth. audio commentary featuring Weber, art director Jack Fisk, costume designer Patricia Norris, and casting director Dianne Crittenden ; new audio interview with Richard Gere ; new video interviews with cinematographers Haskell Wexler and Bailey ; a booklet featuring an essay by critic Adrian Martin and a chapter from director of photography Nestor Almendros's autobiography
Keywords: Farmers - Texas Drama; Triangles (Interpersonal relations) - Texas - Drama; Farmers -- Texas -- Drama; Man-woman relationships -- Drama; Triangles (Interpersonal relations) -- Texas -- Drama; Dreierbeziehung; Landwirt; Texas; Film; Feature films; Video recordings for the hearing impaired; Western films; Melodrama - Feature